PHENOMENOLOGICAL APPROACH TO THE WORD-OF-MOUTH COMMUNICATION IN PRE AND POST TRIP: A STUDY ON INDONESIAN TOURIST VISITED THAILAND - A. Haryo Perwito (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2009)
Satisfied and dissatisfied consumers will create positive or negative Word-of-Mouth communication about their experience on product. This research focuses on Indonesian tourists visiting Thailand, with the objectives, first, to explore the pre-trip information about Thailand as a tourist destination and about its attractions. The second is to explore the post-trip information that the Indonesian tourists would say through Word-of-Mouth communication about Thailand as a tourist destination and its attractions. Interview and observation are used to get the data, and the qualitative analysis with phenomenological approach is used to get the interpretive themes of the received and potential spread-out information. The findings indicated the Indonesia tourists have received minimum information about Thailand and about its attractions. During their trip, beside encountered many disappointment or dissatisfaction reality, they also have got good experiences and views which are followed by admirations. Those experiences will be told to their friends and relatives. It also shown that although they were not satisfied, they still have willingness to revisit and recommend selectively to their friends an relative.